MARKIZ study: screening for post-COVID-19 syndrome using a questionnaire to identify symptoms and risk factors for noncommunicable diseases - N. A. Nikolaev; O. M. Drapkina; M. A. Livzan; Yu. P. Skirdenko; A. Yu. Gorshkov; А. V. Gorbenko; L. Yu. Drozdova; K. A. Andreev; A. I. Blokh; O. V. Gaus; T. D. Zakharova; O. V. Plotnikova; et al. (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To provide data on the diagnostic and prognostic value of questionnaire survey for post-COVID-19 syndrome during screening and regular medical check-ups of employees, as well as preventive medical examinations.Material and methods. This single-center cross-sectional comparative study involved 1120 people (92,1% of the general population — all employees of the organization), including 195 men (67,3% of the general population) and 925 women (79,5% of the general population). All participants filled out the post-COVID-19 syndrome (PS) detection questionnaire, the Hospital Anxiety and Depression Scale and the QAA-25p Adherence Assessment Questionnaire. Potential adherence to treatment was calculated using the SCOPA software. Statistical processing was performed using tools adapted for medical and biomedical research (Python language; Sklearn, NumPy, Pandas libraries) and Statistica 6.13 (StatSoft Inc., USA).Results. As a result, 47% of respondents noted at least one symptom that reduces the quality of life and/or performance efficacy. In all subsamples, women reported symptoms more frequently than men. The most informative indicators associated with post-COVID-19 syndrome are age (Mann-Whitney U test, p=0,042), number of PS symptoms (Mann-Whitney U test, p=0,001), severity of PS symptom (Mann-Whitney U test, p= 0,004) and adherence to health care (Kruskal-Wallis H test, p=0,021). An increased level of anxiety is associated with all the analyzed symptoms, depression level with 6 symptoms, age with 5 symptoms, insufficient compliance with 3 symptoms.Conclusion. PS questionnaire should be included in a comprehensive survey program of persons undergoing medical examinations. It is necessary to develop algorithms for the treatment and diagnosis of patients that take into account the number and severity of individual symptoms separately for men and women with consideration to their COVID-19 epidemiological status, as well as age and markers of anxiety, depression, and adherence to treatment.